Effect of Early Rehabilitation during Intensive Care Unit Stay on Functional Status: Systematic Review and Meta-Analysis. - Ana Cristina Castro-Avila; Pamela Serón; Eddy Fan; Mónica Gaete; Sharon Mickan (PLoS ONE)
Background and aim Critically ill survivors may have functional impairments even five years after hospital discharge. To date there are four systematic reviews suggesting a beneficial impact for mobilisation in mechanically ventilated and intensive care unit (ICU) patients, however there is limited information about the influence of timing, frequency and duration of sessions. Earlier mobilisation during ICU stay may lead to greater benefits. This study aims to determine the effect of early rehabilitation for functional status in ICU/high-dependency unit (HDU) patients. Design Systematic review and meta-analysis. MEDLINE, EMBASE, CINALH, PEDro, Cochrane Library, AMED, ISI web of science, Scielo, LILACS and several clinical trial registries were searched for randomised and non-randomised clinical trials of rehabilitation compared to usual care in adult patients admitted to an ICU/HDU. Results were screened by two independent reviewers. Primary outcome was functional status. Secondary outcomes were walking ability, muscle strength, quality of life, and healthcare utilisation. Data extraction and methodological quality assessment using the PEDro scale was performed by primary reviewer and checked by two other reviewers. The authors of relevant studies were contacted to obtain missing data. Results 5733 records were screened. Seven articles were included in the narrative synthesis and six in the meta-analysis. Early rehabilitation had no significant effect on functional status, muscle strength, quality of life, or healthcare utilisation. However, early rehabilitation led to significantly more patients walking without assistance at hospital discharge (risk ratio 1.42; 95% CI 1.17-1.72). There was a non-significant effect favouring intervention for walking distance and incidence of ICU-acquired weakness. Conclusions Early rehabilitation during ICU stay was not associated with improvements in functional status, muscle strength, quality of life or healthcare utilisation outcomes, although it seems to improve walking ability compared to usual care. Results from ongoing studies may provide more data on the potential benefits of early rehabilitation in critically ill patients.